The Level of Orally Ingested Vitamin C Affected the Expression of Vitamin C Transporters and Vitamin C Accumulation in the Livers of ODS Rats - SONE, Yasuko; UETA, Etsuko; KODAMA, Satoru; SANNOUMARU, Yasuko; MIYAKE, Noriko; SONE, Hirohito; FUJIWARA, Yoko; OTSUKA, Yuzuru; KONDO, Kazuo; INAGAKI, Masahiro; NAMBA, Eiji; KURATA, Tadao; et al. (Bioscience, Biotechnology, and Biochemistry, 2011)
We investigated the effects of vitamin C administration on vitamin C-specific transporters in ODS/ShiJcl-od/od rat livers. The vitamin C-specific transporter levels increased in the livers of the rats not administered vitamin C and decreased in the livers of those administered vitamin C at 100 mg/d, indicating that these transporter levels can be influenced by the amount of vitamin C administered.